An Empirical Study on the Impact of the United States Chile Free Trade Agreement on Chilean Employment and Value Added - Sloan, Adam (Université d'Ottawa | University of Ottawa, 2019)
There is widespread support among economists for greater free trade among the nations of the world. One of the arguments in favour of greater international trade is that if countries focus on producing more of the goods and services for which they have a comparative advantage and trade those goods and services with another country for goods and services that the first country does not have a comparative advantage in both countries will be made better off. This will lead to greater output than if both countries did not participate in trade. In this paper I want to test to see if this conventional view of trade holds empirically. I will be looking at the impact of lower ad valorem tariffs in a large developed economy on the level of employment and value added in a medium-sized developing economy. Specifically, I will be looking at the impact of the United States Chile Free Trade Agreement (USCFTA). I want to measure the impact that the lower import ad valorem tariffs for Chilean industries, when exporting to the United States, had on their levels of employment and value added. the first country does not have a comparative advantage in both countries will be made better off. This will lead to greater output than if both countries did not participate in trade. In this paper I want to test to see if this conventional view of trade holds empirically. I will be looking at the impact of lower ad valorem tariffs in a large developed economy on the level of employment and value added in a medium-sized developing economy. Specifically, I will be looking at the impact of the United States Chile Free Trade Agreement (USCFTA). I want to measure the impact that the lower import ad valorem tariffs for Chilean industries, when exporting to the United States, had on their levels of employment and value added.